FORMATION AND MANAGEMENT OF REGIONAL AGRI-FOOD CLUSTERS IN DEVELOPING COUNTRIES: CASE OF “AGROTRANSILVANIA” (ROMANIA) - MANUKYAN Izabella (Management of Sustainable Development, 2021)
Business clusters are considered to be more applicable in countries classified as developed. However, in modern times developing countries take risks of establishing business clusters and get the expected economic and social rewards. The work observes peculiarities of regional agri-food cluster formation and management in developing countries in the frames of the Romanian “AgroTransilvania” cluster. Based on the empirical analysis and the “CIPM” (“Cluster Initiative Performance Model”) technique, author conducts an expert assessment and finds out how the cluster’s members combine cooperation and competition in order to achieve outstanding results. The research paper encompasses practice-oriented models, including a diamond model for the Romanian agri-food market, a target board of the observed cluster, as well as a map of its members.